2019
DOI: 10.33824/pjpr.2019.34.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Physical Attractiveness and Sexual Esteem Among Male and Female Adult

Abstract: The current study was designed to investigate the relationship of perceived physical attractiveness and sexual esteem among Pakistani women and men. Role of gender and marital status on the study variables was also explored. The sample consisted of 320 adults (130 men and 190 women) with age range of 18 to 35 years. Sample was taken from Islamabad and Rawalpindi. The Multidimensional Body Self Relations Questionnaire – Appearance Scale MBSRQ-AS (Cash, 2000) was used to measure perceived physical attractiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…10). However, Sierra et al (2018) did not find any significant differences in this regard, and neither did Shaheen and Batool (2019). Paradoxically, the latter study did not find any significant differences in the degree of sexual self-esteem as a function of gender but found a relationship between both variables.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…10). However, Sierra et al (2018) did not find any significant differences in this regard, and neither did Shaheen and Batool (2019). Paradoxically, the latter study did not find any significant differences in the degree of sexual self-esteem as a function of gender but found a relationship between both variables.…”
Section: Discussionmentioning
confidence: 66%
“…The literature shows some discrepancies in the relationship between sexual self-esteem and gender. Some authors have not found any differences between women and men (Maas & Lefkowitz, 2015; Shaheen & Batool, 2019; Sierra et al., 2018; Snell & Papini, 1989). By contrast, others such as Peixoto et al.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar mechanisms would operate for optimism or mastery, hostility or aggression, and intelligence. People who are warm, prosocial, and physically attractive are more likely to be hired, and to receive positive evaluations after being hired (Abel, Croysdale, & Stiles, 2009;Kanfer et al, 2001). Legal status not only increases job opportunities, it would provide leverage both to negotiate a higher starting salary, and advocate for subsequent raises.…”
Section: Discussionmentioning
confidence: 99%